Tumor-induced senescent T cells with suppressor function: A potential form of tumor immune evasion - Montes, Carolina Lucia (2008)
Senescent and suppressor T cells are reported to be increased in select patients with cancer and are poor prognostic indicators. Based on the association of these T cells and poor outcomes, we hypothesized that tumors induce senescence in T cells, which negatively effects antitumor immunity. In this report, we show that human T cells from healthy donors incubated with tumor for only 6 h at a low tumor to T-cell ratio undergo a senescence-like phenotype, characterized by the loss of CD27 and CD28 expression and telomere shortening. Tumor-induced senescence of T cells is induced by soluble factors and triggers increases in expression of senescence-associated molecules such as p53, p21, and p16. Importantly, these T cells are not only phenotypically altered, but also functionally altered as they can suppress the proliferation of responder T cells. This suppression requires cell-to-cell contact and is mediated by senescent CD4+ and CD8+ subpopulations, which are distinct from classically described natural T regulatory cells. Our observations support the novel concept that tumor can induce senescent T cells with suppressor function and may effect both the diagnosis and treatment of cancer. ©2008 American Association for Cancer Research.